Alcohol policy impact on young risky drinkers and their support for proposed measures. (25th February 2015) - Lam, Tina; Lenton, Simon R.; Burns, Lucinda; Aiken, Alexandra; Ogeil, Rowan; Gilmore, William T.; Chikritzhs, Tanya N.; Lloyd, Belinda; Lubman, Dan I.; Mattick, Richard; Allsop, Steve J.
Abstract Objective: To explore the impacts of existing policies on young Australian risky drinkers' access to alcohol and to gauge their support for proposed alcohol measures. Methods: The 16–19 year old participants were recruited from three Australian states using non‐random convenience sampling, for either a face‐to‐face or online quantitative survey (N=958). The sample was deliberately selected to represent drinkers whose consumption placed them in the riskiest drinking 20–25% of their age bracket. Results: Half (49%) the sample who were younger than the Australian legal purchase age reported it was 'easy' to buy alcohol from bottle stores, and 75% of those who had tried to purchase alcohol, said it was 'easy' the last time they tried. Half of those under 18, who had attempted to enter a licensed venue, reported they did not have their identification checked last time they gained access. Ninety per cent of all respondents drank within a private location at their last risky drinking session. Sixty‐five per cent supported 'increasing the price of [alcohol by 20¢] a standard drink if the extra 20¢ was used to support prevention and treatment of alcohol problems'. Conclusions: Age‐ or intoxication‐based restrictions to alcohol were commonly bypassed. Implications: Point‐of‐sale alcohol controls require improvement to prevent under age access. Given that a significant proportion of drinking occasions for those under 18 were in private premises, prevention strategies need to target these locations. There were diverse levels of support for strategies to reduce harm, including potential community backing for an evidence‐based proposed price policy.